Characterisation of lateral and vertical subsurface heterogeneity in the ground using sustainable seismic surface wave methodology - Madun, Aziman; Wijeyesekera, Devapriya Chitral; Ahmad Tajuddin, Saiful Azhar; Zainalabidin, Mohd Hazreek; Yunus, Riduan; Tajul Baharudin, Mohamad Faizal (Institute of Physics, 2017)
Seismic surface waves are a non-destructive technique used to obtain the dynamic properties of soil by measuring the shear wave velocity and calculating the shear modulus of soil. The shear modulus is one of the parameters to measure the stiffness of materials. This study evaluates soil profiles and the position of the sensor while conducting measurements of two , soil profiles, i.e. lateral and vertical nonhomogeneities, using a continuous surface wave analysis (CSW) and multi-channel analysis of surface waves (MASW). Results showed the dispersive curve demonstrated an increased shear wave velocity with increasing depth for the sensor pair measurements on the clay (between columns), and decreased shear wave velocity with increasing depth for the sensor pair measurements on the column. In both instances the surface wave velocity results influenced by the depth and size of the wavelength, indicating that depth and wavelength controlled the volume of measurement in an elliptical shape. Therefore, the shear wave velocities and thus stiffness measured from the surface wave velocity techniques are represented the volume of soil measured across the sensor length.